KAJIAN PENINGKATAN KONDISI FISIK ARMADA KAPAL WISATA DANAU DALAM MELAYANI WISATAWAN DI SUMATERA BARAT - Miro, Fidel (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The goal of this study is to strive for the development of Inland Waterway Transport Modes is Lake Transportation in the Great Lakes in the province of West Sumatra. From the results of this study, have to be identified that Lake Transport Operations in the Great Lakes region West Sumatra is not optimal or decreases caused by network connectivity growing tissues lan existing highway around the lake. But if referred to the National Development Direction of Lake Transporton, trying ahead of 2020, the National Transportation Lake cultivated as Inland Waterway Transport Modes to support the Tourism Sector. Then the results of the study recommends that Travel Fleet Superintendent has Dead ri, reformed into a fleet that is able to serve Potential Flow Needs Travelers.